IMPLIKATUR DALAM WACANA KAMPANYE CALON LEGISLATIF KABUPATEN TANAH BUMBU PERIODE 2019—2024: KAJIAN PRAGMATIK - NFN Jahdiah (Balai Bahasa Kalimatan Selatan, 2019)
Election 2019 creats lots of linguistics problems that interesting to be studied. One of them is big poster of legislative candidates. This study discusses about kind of speech act and implicature in every speech of legislative candidates big poster in Tanah Bumbu Regency. The aim of this study is to describe kind of speech act and implicature in every speech of legislative candidates big poster. It is qualitative study using descriptive method. The data are in the form of sentences in the legislative candidates big poster, especially Tanah Bumbu Regency. To analyse the data, this study usesthe theory of peech act and implicature. The result shows that on legislative candidates big poster, there are commisive speech act, directive, expressive, and representative. The implicature that exist in the speech are in the form of inviting, asking for support, persuading, and convincing.